AJARAN GNOSTIK DALAM JEMAAT EFESUS DI SURAT TIMOTIUS DAN TITUS (GNOSTIC TEACHING IN EFESUS CONGREGATIONS IN TIMOTHY AND TITUS LETTERS) - Widjaja, Imron; Simanjuntak, Horbanus Josua; Embong Bulan, Susanti (QUAERENS: Journal of Theology and Christianity Studies, 2019)
This paper discusses the Gnostic teachings which pose a great danger to the true faith of the Ephesians in the Epistles of Timothy and Titus. This gnostic teaching is categorized as heresy and the instructor is called heresy teacher. It was described as pervasive words, like cancer (2 Tim.2: 17). Paul writes of how dangerous the Gnostic teachings and teachers are. They pretend to know, even though they don't know anything. The disease looks for questions and worries, which causes envy, injury, slander, suspicion and strife among people who are no longer healthy and right minded (1 Tim 6: 4-5). That is why, Paul said: "stay away from them!" (2 Tim 3: 5) and in Titus 1: 11a it says, "the people must be shut up." This teaches God's people today to be careful of every teaching, because unhealthy teaching brings God's people into envy, injury, slander, suspicion and strife among people who are no longer healthy and right minded. Tulisan ini membahas ajaran gnostik yang menjadi ancaman bahaya besar terhadap iman sejati jemaat Efesus di Surat Timotius dan Titus. Ajaran gnostik ini dikategorikan sebagai ajaran sesat dan pengajarnya disebut pengajar sesat. Hal itu digambarkan sebagai perkataan yang menjalar, seperti penyakit kanker (2 Tim.2: 17). Paulus menuliskan betapa berbahayanya ajaran dan pengajar gnostik. Mereka berlagak tahu, padahal tidak tahu apa-apa. Penyakitnya suka mencari soal-soal dan bersilat kata, yang menyebabkan dengki, cidera, fitnah, curiga dan percekcokan di antara orang-orang yang tidak lagi berpikiran sehat dan benar (1 Tim 6: 4-5). Itu sebabnya, Paulus berkata: “jauhilah mereka itu!” (2 Tim 3: 5) dan dalam Titus 1: 11a dikatakan, “orang-orang itu harus ditutup mulutnya.” Hal ini mengajarkan kepada umat Tuhan pada saat ini untuk berhati-hati kepada setiap pengajaran, karena pengajaran yang tidak sehat mebawa umat Tuhan kedalam dengki, cidera, fitnah, curiga dan percekcokan di antara orang-orang yang tidak lagi berpikiran sehat dan benar.